2023
DOI: 10.1021/acs.nanolett.2c03809
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Rod-like Tobacco Mosaic Virus Promotes Macrophage Polarization for a Tumor-Suppressive Microenvironment

Abstract: The phenotype of tumor-associated macrophages plays an important role in their function of regulating the tumor immune microenvironment. The M1-phenotype macrophages display tumor-killing and immune activating functions. Here we show that the tobacco mosaic virus (TMV), a rod-like plant virus, can polarize macrophages to an M1 phenotype and shape a tumor-suppressive microenvironment. RAW 264.7 cells and bone marrow derived-macrophages (BMDMs) can recognize TMV via Toll-like receptor-4, and then the MAPK and NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Studies have shown that 1D rod‐shaped TMV itself has certain immunomodulatory properties and can polarize the macrophage M1 subtype to exert tumor killing and immune activation functions, promoting the formation of a tumor‐suppressive microenvironment. [ 45 ] In order to enhance this immunomodulatory ability, a small‐molecule immunomodulator TLR7 antagonist (1V209) was loaded into the inner cavity of TMV, while PDA was wrapped around the outside of TMV. This drug‐loaded system was injected intratumorally and irradiated with 808 nm laser to treat B16F10 skin melanoma.…”
Section: Biomedical Applications Of Tmvcpmentioning
confidence: 99%
“…Studies have shown that 1D rod‐shaped TMV itself has certain immunomodulatory properties and can polarize the macrophage M1 subtype to exert tumor killing and immune activation functions, promoting the formation of a tumor‐suppressive microenvironment. [ 45 ] In order to enhance this immunomodulatory ability, a small‐molecule immunomodulator TLR7 antagonist (1V209) was loaded into the inner cavity of TMV, while PDA was wrapped around the outside of TMV. This drug‐loaded system was injected intratumorally and irradiated with 808 nm laser to treat B16F10 skin melanoma.…”
Section: Biomedical Applications Of Tmvcpmentioning
confidence: 99%
“…49 Ou et al purified tobacco mosaic virus by extraction, precipitation, centrifugation, and dialysis. 120 They discovered that rod-shaped nano-extracts of tobacco mosaic virus polarized macrophages to the M1 phenotype and reversed the protumor microenvironment. The polarization was significantly inhibited when the nanoextract was used in combination with TAK-242 (a TLR4 inhibitor), leading to the downregulation of genes related to CD86, iNOS, TNF-a, IL-6, IL-1b, IL-12b, and CD40.…”
Section: Nanomaterials For Polarizing Macrophages Through a Non-class...mentioning
confidence: 99%
“…TMV has been observed to activate MAPK and NF-κB pro-inflammatory signaling pathways via TLR4, leading to the polarization of macrophages into M1 phenotype and the production of inflammatory cytokines. 87 Nkanga et al utilized TMV to deliver a small-molecule TLR7 antigen for cancer photothermal immunotherapy. 88 In an example of combined immunotherapy and chemotherapy, Lee et al loaded the chemo- therapy drug doxorubicin (DOX) into PVX (Fig.…”
Section: Vlpsmentioning
confidence: 99%